Peningkatan Pemahaman Bahasa Asing pada Perjanjian Akta Notaril Bagi Anggota Ikatan Notaris Indonesia Kabupaten Bandung - Sidik, Jafar; Haspada, Deny; Priyanto, Imam Jahrudin (Jurnal Pengabdian Tri Bhakti, 2021)
Although now the contract is mandatory in Indonesian according to Law no. 24 of 2009, notaries still have to understand notary deeds in foreign languages. In fact, if necessary, be able to make notary deeds using foreign languages. This is necessary to improve the qualifications as a legal apparatus in the field of notarization and land affairs. Moreover, there are quite a lot of notaries in Bandung Regency. Based on data from the Bandung Regency Regional Revenue and Financial Management Service (Dispenda), as of June 2020, there were 418 PPAT (Land Deed Maker Officials) and based on the Notary Portal of Bandung Regency as of June 2020 there were 397 notaries. In accordance with Law no. 2 of 2014 concerning Amendments to Law no. 30 of 2004 concerning the Position of Notary (UUJN), the notary is authorized to make authentic deeds regarding all actions, agreements, and provisions required by laws and regulations and/or those desired by those with an interest to be stated in an authentic deed, guaranteeing the certainty of the date of making the deed, keep the deed, provide a copy and an excerpt of the deed. From the inventory of problems, many notaries do not understand the legal consequences when a notary makes a contract or agreement in the form of a notary deed in a foreign language. It should be noted that a contract or agreement made in the form of a notary deed in a foreign language has certain legal consequences, namely the notary deed is not an authentic deed, but as an underhand deed. In addition, the notary deed has the potential to be filed for cancellation or declared null and void through the state judiciary. The solution is, socialization or legal counseling has been held to notaries regarding the legal umbrella or legal basis for the mandatory use of the Indonesian language in contracts or agreements, either under hand or in the form of a notary deed.